On multiple integral relations involving generalized Mellin-Barnes Type of Contour Integral - Agarwa, Praveen (Tamsui Oxford Journal of Mathematical Sciences)
In this paper, we first evaluate two fi nite basic integrals involving the product of the multivariable polynomial Sh1;:::;hr L [x1; :::; xr] and two generalized Mellin Barnes type of contour integrals. Next, with the help of these basic integrals we establish two integral relations which involve general arguments and are the most general in nature. Again by suitably specializing the function f in the rst integral relation, we have evaluated a multiple integral which is new and quite general in nature. Finally, we present four special cases of our main ndings involving the p q(z), J] ;(z) and Sh L [x], which are also believed to be new. Some known results follow as special cases of our findings.